Preliminary results from breeding experiments with Finnsheep in Poland - Jankowski, S.; Niznikowski, R.; Tyszka, Z. (Agricultural and Food Science, 1988)
Polish Lowland (PL) ewes were mated to Finnsheep x East Friesian (EF) F1 rams to create a synthetic dam line (66), and to Polish Heath x EF F1 rams to create another synthetic dam line (77). Performance of both groups were recorded and compared to purebred PL (88). The numbers of animals in the composite lines were too small for statistical analyses and conclusive results. Contrary to expectations line 77 excelled line 88 in lambing rate by 3 %, while line 66 was inferior to it. In litter size, both composite lines slightly excelled line 88. Line 66 excelled line 88 in lamb survival, while line 77 was a little inferior to it. In fleece weights, line 66 was equal with line 88, but line 77 lagged 24 % behind. Both of the composite lines excelled line 88 in daily gain by 10 %, being rather similar to each other.